Molecular recognition of siderophores in fungi: role of iron-surrounding N-acyl residues and the peptide backbone during membrane transport in Neurospora crassa. - Huschka, H G (1986)
Recognition of ferric siderophores in Neurospora crassa was found to depend on the number and kind of N-acyl residues that surrounded the iron coordination center. In the coprogen series, uptake decreased in the order of coprogen, neocoprogen I, and neocoprogen II, indicating that gradual replacement of the N-transanhydromevalonyl groups by N-acetyl groups had an adverse effect on uptake. The reverse effect was observed in the ferrichrome series, where uptake decreased in the order of ferrichrysin, asperchrome D1, asperchrome B1, and ferrirubin. Configuration of the anhydromevalonyl group (cis or trans) in ferrichromes was also an important determinant in the recognition process. On the basis of uptake and inhibition studies, it is proposed that in ferrichromes part of the molecule (iron configuration and the N-acyl groups) is responsible for binding, whereas another (cyclic peptide ring) is involved in the subsequent process of transport.